Implementasi Kebijakan Peraturan ANRI 6/2021 pada Fungsi Kearsipan Sekretariat Ditjen Kementerian X RI - Zahara, Namira Rahmi; Mayesti, Nina (UI Scholars Hub, 2024)
This study discusses the Policy Implementation of ANRI Regulation 6/2021 on The Archives Functions of the Secretariat of the Directorate General of Ministry X RI by using the concept of policy implementation George C. Edward III, namely communication, resources, disposition, and bureaucratic structure. This research uses a qualitative approach with a case study method. This study concludes that implementing the ANRI 6/2021 regulation at the Secretariat of the Directorate General still needs to improve or is not optimal in every influencing factor. This research suggests that the Secretariat of the Directorate General needs commitment, honesty, and also a perspective in providing the same EAM information from leaders to implementers in implementing policies, UK1 as archivist supervisor at Ministry X in order to speed up the process of making derivative regulations in the form of Minister X Regulations regarding EAM.